2015
DOI: 10.3329/bjas.v44i2.26011
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition of para-grass (Brachiaria mutica) produced in integrated fish-fodder culture system

Abstract: An experiment was conducted to evaluate the effects of Pangasius pond sediment on the nutrient uptake by para-grass (Brachiaria mutica) during the period from March to October, 2011 in a Pangasius farm, Dhanikhola, Trishal, Mymensingh. Initially soil chemistry of Pangasius pond sediment and para-grass producing virgin soil was analyzed at the laboratory. The fodder was cultivated at various level of inorganic fertilizer with Pangasius pond sediment having three replications in each treatment. The size of each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
1
2
4
Order By: Relevance
“…In the present study, carbohydrate content in all the species was found to be in the range of 17.44–37.27 mg/100 mg, which was significantly higher ( p < 0.05) in M. falcate (37.27 mg/100 mg) and T. pratense (31.13 mg/100 mg) as compared with F. kashmiriana (30.97 mg/100 mg), M. indica (26.23 mg/100 mg) and M. sativa (17.44 mg/100 mg). Our data are comparable with those reported for Brachiaria mutica from Dhanikhola, Bangladesh, having carbohydrate content in the range of 23.40–30.91 mg/100 mg (Alam et al, 2015), suggesting that these forage species could be considered as a potential source of energy and used as stimulating factor for dairy cattle production. The CP is an another important parameter of nutritional quality that represents nitrogen pool and provides raw material for AA and nucleotide synthesis.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, carbohydrate content in all the species was found to be in the range of 17.44–37.27 mg/100 mg, which was significantly higher ( p < 0.05) in M. falcate (37.27 mg/100 mg) and T. pratense (31.13 mg/100 mg) as compared with F. kashmiriana (30.97 mg/100 mg), M. indica (26.23 mg/100 mg) and M. sativa (17.44 mg/100 mg). Our data are comparable with those reported for Brachiaria mutica from Dhanikhola, Bangladesh, having carbohydrate content in the range of 23.40–30.91 mg/100 mg (Alam et al, 2015), suggesting that these forage species could be considered as a potential source of energy and used as stimulating factor for dairy cattle production. The CP is an another important parameter of nutritional quality that represents nitrogen pool and provides raw material for AA and nucleotide synthesis.…”
Section: Resultssupporting
confidence: 90%
“…Oke et al (2016) reported lower CP content percentage in Durba (8.60) than the present findings. Lower CP content percentage of Para (3.30) was reported by Alam et al (2015). But higher CP content percentage of Para was reported by Kanak et al (2013) (8.9) than the present findings.…”
Section: Chemical Composition Of Roughage Samplescontrasting
confidence: 67%
“…Lower DM content percentage in Durba (23.22) was also recorded by Oke et al (2016). Higher amount of DM content percentage of Para (48.00) was reported by Alam et al (2015) than the present findings. The crude protein content percentage of Durba (11.30) in the present study is almost similar to the findings of Manzoor et al (2013) (11.30).…”
Section: Chemical Composition Of Roughage Samplescontrasting
confidence: 49%
“…Meanwhile, the ash content of grasses in lowland areas ranged from 6.32 to 8.91% (Richmond et al 2015;Mako et al 2016;Norman et al 2013;Maswada et al 2013). Alam et al (2015) found that B. mutica had an ash content of 4.20-4.89% and rice straw had 6.63%.…”
Section: Ash Contentsmentioning
confidence: 99%